Study Of Indirect Fibromarkers inIdentifying theDegree ofLiver Fibrosis During Antiviral Therapy Of Patients With Hepatitis HCV Etiology (Texas Journal of Medical Science, 2024)
This  work  examined  the  diagnostic  role  of  biomarkers -APRI, alpha-fetoprotein–AFP  and gammaglutamine transpeptidase–GGTP before and after antiviral therapy in patients with different degrees of liver fibrosis. At the same time, there was a decrease in these indicators after treatment, which indicates a reverse development of liver fibrosis after specific therapy.During therapy, a significant decrease in APRI from 0.67 to 0.33 (p